Lentiviral shRNA Construction in Gene Therapy for Knock Down CYPIA1, and YWHAZ gene in Lung Cancer - Henik Anjayati (Journal of Biological Science and Education, 2021)
Lung cancer is a disease that is in the top 10 causes of death globally. It is caused by CYP1A1 and YWHAZ genes expressed in the lungs. One of the solutions offered for lung cancer sufferers is gene therapy. Gene therapy for lung cancer is focused on the knock-down of expressed CYP1A1 and YWHAZ genes. It can be using shRNA transfected into lung cells by lentivirus. The lentivirus envelope is modified using glycoprotein filovirus, one of which is ebolavirus. Lentivirus pseudotyping can recognize certain cells. Especially, Ebolavirus can recognize lung cells. The lentiviral gene is designed to carry the gene of interest (shRNA) but no the infectious gene. The shRNA gene transfused into lung cancer cells will recognize and complement the specific target mRNA sites of the CYP1A1 and YWHAZ genes. After that, shRNA will cut the mRNA which should be expressed into a cancer protein. Unexpressed mRNA into protein causes cancer cell growth inhibited. Thus, this gene therapy solution is expected to be able to reduce the rate of death caused by lung cancer. Keywords: Lung cancer, CYP1A1 and YWHAZ genes, gene therapy, lentiviral, shRNA